Molecular Biological Tools in Cancer Diagnostics with a Case Study (International Journal of Scientific Research and Management (IJSRM), 2020)
Projects of cancer diagnostics are significantly variegated. Manifestly, however, understanding molecular biology can accomplish a great deal in the midst of any diagnostic strategy. This report will seek to indicate some of the key bases of molecular biomedical study, including the foundations of cell growth, cell death, and genetics, together with specific instances of protein classification, as they pertain to cancer. Methodologies of cancer analysis and treatment that cover similar molecular ground will then be elucidated. This will all serve to anchor an examination of the MET/phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mechanistic target of rapamycin (mTOR) pathway, linked to problematic cell proliferation in oncogenesis.